Thermodynamic Features of Diethyl Citrate Calcium Complexes and Factors Affecting the Complex Stability - Ou, Yan; Chen, Bin; Peng, Hua; Gui, Bao-Song; Yao, Xiu-Qiong; Ouyang, Jian-Ming (Asian Journal of Chemistry, 2012)
Diethyl citrate (Et2Cit) is a promising new anticoagulant. In this study, the stoichiometry of the Et2Cit complex with Ca2+ ions and the stability constant (Ks) were determined. The effect of pH and temperature on Ks were then discussed. Thermodynamic functions (DG, DH, DS) of the complex were also calculated. These results were compared with those of sodium citrate (Na3Cit), a current clinical anticoagulant. Both Et2Cit and Na3Cit formed complexes with Ca2+ ion at 1:1 ratio. The Ks measured for calcium diethyl citrate (CaEt2Cit) and calcium citrate (CaCit) was 231 and 1988, respectively, at pH 7.4, 37 ºC. It is indicated that CaCit was more stable than CaEt2Cit. Increasing pH or solution temperature favoured the formation of both complexes. Increasing temperature from 15 to 40 ºC led to a shift of Ks from 58 up to 327 for CaEt2Cit and 327 up to 2327 for CaCit, as a result of their endothermic reactions. Animal testing results on rabbits showed that the recovery speed of blood calcium concentration with Et2Cit as anticoagulant was more rapid than that with Na3Cit. Et2Cit is expected to circumvent the problems of hypocalcemia and hypercalcemia which are usually encountered when using Na3Cit for anticoagulation. Therefore, Et2Cit has shown great potential as a new anticoagulant.